2020
DOI: 10.3390/app10051725
|View full text |Cite
|
Sign up to set email alerts
|

Nannochloropsis oceanica Cultivation in Pilot-Scale Raceway Ponds—From Design to Cultivation

Abstract: Raceways ponds are the microalgal production systems most commonly used at industrial scale. In this work, two different raceway configurations were tested under the same processing conditions to compare their performance on the production of Nannochloropsis oceanica. Biomass productivity, biochemical composition of the produced biomass, and power requirements to operate those reactors were evaluated. Water depths of 0.20 and 0.13 m, and culture circulation velocities of 0.30 and 0.15 m s−1 were tested. A stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…San Pedro et al (2014) reported lipid productivity values between 50-60 mg L −1 day −1 in a 340 L vertical tubular PBR operated in continuous mode using a 0.1 day −1 dilution rate under similar weather conditions. The higher values are due to higher biomass productivity achieved by the authors, since the attained lipid content was similar (20-30%) [15] The lipid content values reached in the present study in a tubular PBR for N. oceanica (19.1-24.0%) were higher than the ones obtained by Cunha et al (2020) (13.2-19.0%), in a raceway reactor using the same strain, in the same location and time of the year [40]. This result highlights that the tubular horizontal PBR produces biomass with higher quality for biofuel than that cultivated in open systems.…”
Section: Biochemical Profilesupporting
confidence: 51%
“…San Pedro et al (2014) reported lipid productivity values between 50-60 mg L −1 day −1 in a 340 L vertical tubular PBR operated in continuous mode using a 0.1 day −1 dilution rate under similar weather conditions. The higher values are due to higher biomass productivity achieved by the authors, since the attained lipid content was similar (20-30%) [15] The lipid content values reached in the present study in a tubular PBR for N. oceanica (19.1-24.0%) were higher than the ones obtained by Cunha et al (2020) (13.2-19.0%), in a raceway reactor using the same strain, in the same location and time of the year [40]. This result highlights that the tubular horizontal PBR produces biomass with higher quality for biofuel than that cultivated in open systems.…”
Section: Biochemical Profilesupporting
confidence: 51%
“…Therefore, culture depth is an important parameter in open raceway ponds that may affect not only microalgal growth but also biochemical composition of the cells. It was reported that a culture depth of 12-15 cm was optimal for production of algal storage lipids [46,47] and secondary carotenoids [48]. In this study, however, the optimal culture depth was 20-25 cm for a maximum cellular EPA content of 3.4% (w/w) and a higher EPA productivity of 344.5 mg m −2 d −1 than that obtained from the cultures maintained at 10-15 cm depth (i.e., 3.1% EPA and EPA productivity of 290 mg L −1 d −1 ) (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Suitable mixing is, therefore, critical for productive algae cultivation. On a large scale, mixing is generated by paddlewheels in ponds [ 94 ] and pumps in closed systems. As pumps are becoming more energy-efficient, their application increases even in ponds.…”
Section: Light Availability and Mixingmentioning
confidence: 99%